Research on the Emotional Evolution Mechanism of Network Public Opinion Based on an Information Ecosystem. (29th August 2022) - Qu, Ying; Tian, Hongmei; Chen, Hong
Abstract : As an important carrier of public emotion expression, public opinion spreads on a large scale with the continuous upgrading of social networks, and effectively controlling the spreading process of public opinion is an essential topic of contemporary social research. In view of the competition between positive and negative information in the process of public opinion dissemination, this paper introduces the theory of emotional infection and proposes a network public opinion communication model based on emotional contagion, considering the reinforcement effect of different individual mentalities and the influence of government intervention. Based on the data from the COVID-19 epidemic situation, MATLAB simulation technology is used to verify the validity of the model, and the effect of strengthening the validity and government intervention on public opinion control is discussed. According to the experiment, three conclusions have been come up with. First, a positive reinforcement effect can enhance the ignorant participants' ability to maintain the same emotion as the infected information. When positive information repeatedly stimulates the ignorant, it will positively strengthen the ability of people with a positive mentality to maintain positive emotions, which is significantly beneficial to public opinion control. Its essence is to increase the effect of positive information's belief factor on the dynamic infection rate. When negative information repeatedly stimulates an ignorant person, it will positively strengthen the ability of the person with a negative attitude to maintain negative emotion, which is not conducive to public opinion control. Second, a negative reinforcement effect will strengthen the ignorant ability to change the same emotion as the infected information. When negative information repeatedly stimulates the ignorant, the negative reinforcement effect will strengthen the positive people's ability to change negative information into positive emotion, which is significantly beneficial to public opinion control. Its essence is to increase the effect of suspicion factor on the dynamic immunization rate. It will strengthen the positive mentality and negative mentality into the path of immunization, which is beneficial to epidemic control. When positive information repeatedly stimulates the ignorant, it will negatively strengthen the ability of the negative mentality to change the positive information into negative emotions, which is not beneficial to the control of public opinion. It will be harmful to strengthen the path of positive and negative mentality into immunization, which is beneficial to epidemic control. Third, the earlier the government intervenes in public opinion, the better it will be. The essence of intervention is to decrease the dynamic incitement rate.